In-success factor for project management in high-rise building project - Yahya Al-Tawil, Yahya Mohsen (2019)
Success of each project and efficiency is required to achieve a greater advantage over the firms in construction industry today. Effective project management overcomes these types of challenges such as good communication and good planning and scheduling. Each big construction project company strives to achieve the most efficient and effective project management processes. The success factors which are important for project management in high rise building project success to prevent the project delay, however the main issues that can lead the project to fail is lack of communication among the project team. This study identifies the project management practices in high rise building, success factor for project management on high rise building and un-success factor for project management. The methodology of this study uses questionnaire method and the targeted are G7 contractors’ firms in Johor Bahru with number of 60 respondents. This study uses descriptive statistical analysis which is frequency and mean by SPPS software. The dominant practice from the analysis for the first objective is comprehensive understanding of the work and process. While, the dominant success factor from the analysis for the second objective are project manager ability to coordinate and motivate team. Finally, the dominant factor from the analysis for the third objective un-success factor which is financial difficulties faced by the contractor. Further study can be performed regarding this topic in different ways or methods such as other provinces or cities of Malaysia; another type of construction projects, such as highways construction project, dam construction project, using another grade of contractors such as G6, G5 and etc.